EFFECTS OF PREPARATION CONDITIONS ON ANTIOXIDANT POTENTIAL OF SOME HERBAL TEAS - F. G. Akcakaya; L. Y. Aydemir (Journal of Animal and Plant Sciences, 2019)
In this study, the effects of extraction temperature (X1; 95-100°C) and time (X2; 5-10min), and storage time (X3;0-12 day in refrigerator) on total phenolic content (TPC), free radical scavenging (FRSA) and iron chelating (ICA) activities of dried cinnamon bark, clove, and hibiscus infusions and decoctions were determined constructing 2-level factorial design. TPC, FRSA, and ICA of infusions and decoctions were significantly changed depending on X2 and X3. Hibiscus infusions and decoctions had the highest TPC and FRSA in all parameters. The highest antioxidant activities were measured for 5-min decoctions.  Strong positive Pearson’s correlations were determined between TPC and FRSC of extracts (P≤0.01). After storage, significant changes were determined in TPC, FRSA, and ICA of extracts. Generally sharp decreases were observed in TPC of extracts after storage. Hibiscus infusions and decoctions were the most instable extracts. The highest FRSA stabilities or increments were determined for clove infusions and decoctions. All decoctions had significantly higher FRSA after storage. Strong positive Pearson’s correlations were determined between TPC and FRSA stabilities. This study revealed the potential of infusions and decoctions of clove, cinnamon, and hibiscus as natural antioxidant drinks in daily life
Keywords: Antioxidant activity; cinnamon; clove; decoctions; hibiscus; infusion